The Competent Administrative Authority In the Management of the General Facility of Oil and gas in the Iraqi Legislation - Al-Shamaa, Huda; Hamza, Waleed (Journal of Legal Sciences, 2023)
In this research, we will deal with the administrative body concerned with the management, exploitation and regulation of oil activity and oil operations, which the Iraqi legislation in force dealt with in terms of composition and tasks. And the Ministry of Natural Resources and public companies specialized in oil affairs, and both facilities operate independently without unified cooperation or guidance between them, with the union of the subject of activity, which is the oil and gas wealth owned by the entire Iraqi people. Where it was noted that there are two authorities that use the method of centralization and decentralization in the management of oil operations, and it was also noted that there is a mismatch between the legislation regulating the hydrocarbon wealth in Iraq and the existing one, which necessitated a review of the legislation currently in force or its consideration in the draft of the current oil and gas law.